Method for detecting doxorubicin hydrochloride by using pd-au / mos2 / go composite nanomaterial
Patent Information
- Application Number
- CN202410040188.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-11
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-01-11
AI Technical Summary
但是,由于一些毒性副作用,包括心脏毒性,脱发,骨髓抑制,低白蛋白血症,盐酸阿霉素的临床应用受到限制
(1)采用本发明的方法成功的制备了Pd-Au/MoS2/GO复合纳米材料,将制备的Pd-Au/MoS2/GO复合纳米材料用于构建电化学传感器检测盐酸阿霉素,结果表明Pd-Au/MoS2/GO复合纳米材料具有较好的电化学活性能够实现对盐酸阿霉素的检测,并能实现对实际样品中盐酸阿霉素的加标回收检测。
Smart Images

Figure CN117783241B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of anticancer drug detection, and in particular to the preparation of Pd-Au / MoS2 / GO composite nanomaterials and their detection method for doxorubicin hydrochloride. Background Technology
[0002] Doxorubicin hydrochloride (DOX) is an important anticancer drug widely used in clinical treatment of breast cancer, lymphoma, and bladder cancer. However, its clinical application is limited due to several toxic side effects, including cardiotoxicity, hair loss, bone marrow suppression, and hypoalbuminemia. Therefore, it is necessary to monitor the concentration of doxorubicin hydrochloride in patients' serum or urine to avoid adverse reactions and ensure the effectiveness of treatment and patient safety. Currently, electrochemical analysis methods are widely used in sample detection due to their advantages such as simple equipment, easy operation, low cost, fast analysis speed, and high sensitivity. Summary of the Invention
[0003] To address the aforementioned problems, this invention provides a Pd-Au / MoS2 / GO composite nanomaterial with excellent electrochemical performance and stability, and uses it to modify a glassy carbon electrode to construct an electrochemical sensor based on the Pd-Au / MoS2 / GO composite nanomaterial for the rapid detection of doxorubicin hydrochloride.
[0004] The present invention proposes the following technical solution: According to one aspect of this application, a method for preparing MoS2 / GO composite nanomaterials is provided, comprising the following steps: Preparation of MoS2 / GO nanomaterials; In some embodiments, a certain mass ratio of GO, Na2MoO4 and CH4N2S is dissolved in water and dispersed evenly. Then, the dispersion is transferred to a high-pressure reactor, heated to a predetermined temperature, kept at the temperature, separated, and washed to obtain MoS2 / GO composite nanomaterials.
[0005] In some embodiments, the mass ratios of GO, CH4N2S, and Na2MoO4 are 1:7.96:6.38, 1:7.00:5.10, 1:5.97:4.80, and 1:5.00:3.98, respectively.
[0006] In some embodiments, the GO, Na2MoO4 and CH4N2S solutions are transferred into a high-pressure reactor, mixed and heated at 200°C for 24 hours.
[0007] According to another aspect of this application, a MoS2 / GO composite nanomaterial prepared by the aforementioned method is provided.
[0008] According to another aspect of this application, a method for preparing Pd-Au / MoS2 / GO composite nanomaterials is provided, comprising the following steps: Pd-Au nanoparticles were loaded onto the aforementioned MoS2 / GO composite nanomaterial to obtain the Pd-Au / MoS2 / GO composite nanomaterial.
[0009] In some embodiments, the method for preparing Pd-Au / MoS2 / GO composite nanomaterials includes the following steps: MoS2 / GO and C6H5Na3O7·2H2O were dissolved in deionized water and kept at a constant temperature in a water bath. A precursor solution of HAuCl4·4H2O was added and the mixture was stirred for a certain period. Then, K2PdCl6 and ascorbic acid were added, and the reaction continued until the precursor solution was completely reduced. After centrifugation and washing, Pd-Au / MoS2 / GO composite nanomaterials were obtained.
[0010] In some embodiments, MoS2 / GO and C6H5Na3O7·2H2O are dissolved in deionized water and kept at a constant temperature of 98 °C in a constant temperature water bath.
[0011] In some embodiments, the mass ratios of MoS2 / GO, HAuCl4·4H2O, and K2PdCl6 are 100:0.91:0.0046, 100:0.23:0.0011, and 100:0.16:0.00076, respectively.
[0012] In some embodiments, the reaction time after adding HAuCl4·4H2O precursor solution is 20-40 min.
[0013] In some implementations, after adding K2PdCl6 and ascorbic acid, the temperature and stirring time is continued for 1.5 h to 4 h. According to another aspect of this application, a Pd-Au / MoS2 / GO composite nanomaterial prepared by the method described above is provided.
[0014] According to another aspect of this application, an electrochemical sensor is provided that utilizes a glassy carbon electrode modified with the aforementioned Pd-Au / MoS2 / GO composite nanomaterial.
[0015] According to another aspect of this application, there is provided an application of the aforementioned electrochemical sensor in the detection of doxorubicin hydrochloride.
[0016] The beneficial effects of this invention are: (1) Pd-Au / MoS2 / GO composite nanomaterials were successfully prepared using the method of the present invention. The prepared Pd-Au / MoS2 / GO composite nanomaterials were used to construct an electrochemical sensor for the detection of doxorubicin hydrochloride. The results showed that the Pd-Au / MoS2 / GO composite nanomaterials had good electrochemical activity and could realize the detection of doxorubicin hydrochloride, and could realize the spiked recovery detection of doxorubicin hydrochloride in actual samples.
[0017] (2) The introduction of Pd-Au greatly improves the electrochemical activity of the prepared composite nanomaterial, giving it better electrochemical performance in detecting doxorubicin hydrochloride. Attached Figure Description
[0018] Figure 1 SEM images of MoS2 / GO prepared from different reactants; Figure 2 SEM images of Pd-Au / MoS2 / GO prepared under different reaction conditions; Figure 3 XRD patterns of MoS2 / GO and Pd-Au / MoS2 / GO; Figure 4 CV plots of Pd-Au / MoS2 / GO / GCE in PBS buffer solution at pH=7.4 without 30 µM doxorubicin hydrochloride (a) and with 30 µM doxorubicin hydrochloride (c), (b) CV plot of MoS2 / GO / GCE in PBS buffer solution with 30 µM doxorubicin hydrochloride; Figure 5 (A) CV plots of Pd-Au / MoS2 / GO / GCE in different PBS buffer solutions containing 30 µM doxorubicin hydrochloride, at pH values of 5.7, 6.1, 6.5, 7.0, 7.4, 8.0 and 8.5; (B) Relationship between oxidation peak potential and pH. Figure 6 (A) CV curve of Pd-Au / MoS2 / GO / GCE in PBS buffer solution at pH=7.4 containing 30 µM doxorubicin hydrochloride, with scan rates of 40, 50, 60, 70, 80, 90, 100, 120, 140, 160, 180, 200, 250, 300, 350, and 400 mV / s; (B) Relationship between oxidation peak current of doxorubicin hydrochloride and scan rate; Figure 7 (A) DPV plots of Pd-Au / MoS2 / GO / GCE in PBS buffer solution at pH 7.4 for different concentrations of doxorubicin hydrochloride (1.04, 6.6, 20.7, 30, 38.7, 46.9, 54.5 μmol / L); (B) Relationship between oxidation peak current and concentration. Detailed Implementation
[0019] The present invention will be further described below with reference to the embodiments, but the present invention is not limited to the embodiments.
[0020] Example 1: Synthesis of MoS2 / GO 19.6 mg GO, 0.0804 g Na₂MoO₄, 0.1015 g CH₄N₂S, and 19.6 mL of deionized water were added to a beaker and ultrasonically dispersed for 30 min to ensure complete dissolution and thorough mixing. The dispersion was then placed in a high-pressure reactor and reacted at 200 °C for 24 h. After the reaction was complete, the resulting black solution was washed three times with deionized water and anhydrous ethanol by centrifugation, and ultrasonically dispersed in 40 mL of deionized water to obtain MoS₂ / GO. Simultaneously, the amounts of reactants were optimized, and the amounts of thiourea and sodium molybdate were adjusted to prepare MoS₂ / GO. The values 1, 2, 3, and 4 represent m... GO :m 硫脲 :m 钼酸钠 The MoS2 / GO prepared by ratios of 1:5.00:3.98, 1:5.97:4.80, 1:7.00:5.10, and 1:7.96:6.38, with specific reagent amounts shown in Table 1.
[0021]
[0022] Example 2 Synthesis of Pd-Au / MoS2 / GO nanomaterials Add 2 mL (50 mg / mL) MoS2 / GO, 300 mg C6H5Na3O7·2H2O, and 18 mL of deionized water to a three-necked flask. Place the flask in a constant temperature water bath and heat to 98 °C with stirring at 1000 rpm. Add 0.05 mL HAuCl4·4H2O (148.96 mmol / L) and react for 20 min. Then add 0.13 mL K2PdCl6 (76.6 mmol / L) and 1 mL 0.1 g / mL ascorbic acid solution, and continue the reaction until HAuCl4·4H2O and K2PdCl6 react completely. Wash three times with deionized water and anhydrous ethanol by centrifugation, and then sonicate to disperse in 5 mL of deionized water to obtain Pd-Au / MoS2 / GO.
[0023] During the experiment, the amount of noble metal precursor solution was optimized. While keeping the amount of MoS2 / GO constant, the amount of noble metal precursor solution was adjusted, and the reaction temperature was changed to prepare four different Pd-Au / MoS2 / GO nanomaterials. The prepared nanomaterials were numbered a, b, c, and d, respectively. The amount of noble metal precursor solution and the reaction temperature are shown in Table 2.
[0024]
[0025] The MoS2 / GO nanomaterials in Example 1 were characterized by scanning electron microscopy, and the characterization results are as follows.
[0026] The morphological characteristics of MoS2 / GO composite nanomaterials prepared under different conditions were analyzed by SEM. Figure 1 Scanning electron microscope images of MoS2 / GO prepared with different amounts of GO, thiourea, and sodium molybdate. Figure 1 -A is m GO :m 硫脲 :m 钼酸钠 Figure B shows the SEM image of the MoS2 / GO prepared with a ratio of 1:5.00:3.98. The image reveals that the clustered MoS2 surface is coated with a thick, transparent film of GO, and the MoS2 distribution is uneven. Figure B shows the m... GO :m 硫脲 :m 钼酸钠 SEM images of MoS2 / GO prepared at a ratio of 1:5.97:4.80 show that as the amount of sodium molybdate increases, the amount of MoS2 in the product also increases, while GO still forms a thick film coating around the MoS2. Figure C shows m GO With m 硫脲 :m 钼酸钠 SEM images of MoS2 / GO prepared at a ratio of 1:6.99:5.1 show that GO is uniformly coated on the surface of MoS2 in a thin film, and the MoS2 particles are of uniform size and distribution. Figure D shows the m... GO With m 硫脲 :m 钼酸钠 SEM images of MoS2 / GO prepared at a ratio of 1:7.96:6.38 show that as the amount of sodium molybdate continues to increase, a large amount of MoS2 and GO aggregates and attaches to the GO. The results indicate that when m... GO :m 硫脲 :m 钼酸钠 When the ratio is 1:6.99:5.10, the prepared MoS2 / GO has a better morphology and structure.
[0027] The Pd-Au / MoS2 / GN nanomaterials in Example 2 were characterized by scanning electron microscopy, and the characterization results are as follows.
[0028] With m GO :m 硫脲 :m 钼酸钠 Pd-Au / MoS2 / GN was prepared using MoS2 / GN nanomaterials with a ratio of 1:6.99:5.10 as raw material. The mass ratio of MoS2 / GN to the noble metal precursor solution was optimized. SEM characterization was performed as follows. Figure 2 As shown. Figure 2Figure A shows the SEM image of Pd-Au / MoS2 / GN sample a. It can be observed that some aggregated Au NPs and Pd NPs are loaded on MoS2 / GN, and the distribution of Au NPs and Pd NPs is relatively uneven. Figure B shows the SEM image of Pd-Au / MoS2 / GN sample b. It can be observed that a small amount of Au NPs and Pd NPs still aggregate. Figure C shows the SEM image of Pd-Au / MoS2 / GN sample c. It can be seen that Au NPs and Pd NPs are distributed orderly and uniformly on the MoS2 / GN surface, without obvious aggregation. Figure D shows the SEM image of Pd-Au / MoS2 / GN sample d. As can be seen from the figure, most of the Au NPs and Pd NPs agglomerated into large particles. The results indicate that the Pd-Au / MoS2 / GN nanomaterials prepared at a reaction temperature of 98℃ with 3.07 mg of HAuCl4·4H2O and 3.96 mg of K2PdCl6 have good morphology and structure, and the Pd-Au nanoparticles are uniformly distributed.
[0029] Phase analysis was performed on the MoS2 / GN nanomaterials prepared in Example 1, and the characterization results are as follows: Phase analysis of the prepared MoS2 / GN composite nanomaterials was performed using X-ray diffraction (XRD). Figure 3 As shown in curve a, there are obvious characteristic diffraction peaks at 13.9°, 33.2°, 37.1°, and 58.6°, corresponding to the (002), (100), (103), and (110) crystal planes of MoS2, which is consistent with the results of the MoS2 standard card (JCPDS 37-1492). In addition, a significant diffraction peak was also observed at 10.5°, which is a characteristic diffraction peak of GO in MoS2 / GO.
[0030] Phase analysis was performed on the Pd-Au / MoS2 / GN nanomaterials prepared in Example 2, and the characterization results are as follows: like Figure 3 As shown in curve b, distinct diffraction peaks appear at 38.1°, 44.3°, 64.5°, and 77.5°, corresponding to the (111), (200), (220), and (311) crystal planes of Au NPs, consistent with the results of the Au NPs standard card (JCPDS 04-0784). Furthermore, distinct characteristic diffraction peaks are observed at 40.0°, 46.5°, 68.0°, and 81.8°, corresponding to the (111), (200), (220), and (311) crystal planes of Pd NPs, consistent with the results of the Pd NPs standard card (JCPDS 46-1043). These results demonstrate the successful synthesis of Pd-Au / MoS2 / GO composite nanomaterials.
[0031] Example 3: Pd-Au / MoS2 / GO composite nanomaterials modified glassy carbon electrode First, the glassy carbon electrode (GCE) was polished on chamois leather with an appropriate amount of Al2O3 powder, rinsed with distilled water, and then dried with nitrogen. The prepared Pd-Au / MoS2 / GO composite nanomaterial was prepared into a solution with a concentration of 1 mg / mL, ultrasonically dispersed, and then 7 μL of the composite nanomaterial was used to modify the surface of the glassy carbon electrode. It was then air-dried at room temperature and stored for later use.
[0032] Example 4: MoS2 / GO composite nanomaterials modified glassy carbon electrode First, the glassy carbon electrode (GCE) was polished to a mirror finish on chamois leather with an appropriate amount of Al2O3 powder, rinsed clean with distilled water, and then dried with nitrogen. The prepared MoS2 / GO composite nanomaterial was prepared into a solution with a concentration of 1 mg / mL, ultrasonically dispersed, and then 7 μL of the composite nanomaterial was used to modify the glassy carbon electrode. It was then air-dried at room temperature and stored for later use.
[0033] Example 5 Electrochemical characterization of the sensor
[0034] Cyclic voltammetry was measured in PBS buffer solutions containing doxorubicin hydrochloride and doxorubicin hydrochloride at a scan rate of 100 mV / s.
[0035] like Figure 4 As shown, curve a is the cyclic voltammogram of Pd-Au / MoS2 / GO / GCE in a PBS buffer solution without 30 µM doxorubicin hydrochloride. It can be seen that without doxorubicin hydrochloride, there is no obvious redox peak in the potential range of -0.4 V to 0.6 V. Curve b is the cyclic voltammogram of MoS2 / GN / GCE in a PBS buffer solution containing 30 µM doxorubicin hydrochloride. It can be seen from the figure that its redox peak is also not obvious. Curve c is the cyclic voltammogram of Pd-Au / MoS2 / GO / GCE in a PBS solution containing 30 µM doxorubicin hydrochloride. It can be seen from the figure that a significant oxidation peak can be seen near 0.04 V; this indicates that the Pd-Au / MoS2 / GN composite nanomaterial has high electrocatalytic activity for the detection of doxorubicin hydrochloride. Example 6
[0036] The electrochemical sensor prepared in Example 3 was used to investigate the effect of pH on the detection of doxorubicin hydrochloride in PBS buffer solutions containing 30 µM doxorubicin hydrochloride at different pH values (5.7, 6.1, 6.5, 7.0, 7.4, 8.0, 8.5) using cyclic voltammetry.
[0037] To obtain a better electrochemical response signal of Pd-Au / MoS2 / GO to doxorubicin hydrochloride, the effect of pH on the detection of doxorubicin hydrochloride was optimized using cyclic voltammetry in a PBS buffer solution containing 30 µM doxorubicin hydrochloride at a scan rate of 100 mV / s. Figure 5 As shown, the peak current first increases and then decreases with increasing pH, reaching its maximum at pH 7.4. Therefore, PBS buffer solution at pH 7.4 was used as the detection substrate throughout the experiment. Furthermore, the figure shows that the redox peak potential of doxorubicin hydrochloride shifts negatively with increasing pH, indicating that H... + Ions participate in oxidation reactions. Figure 5 B represents the graph showing the relationship between peak potential and different pH values. The linear relationship can be described by the following equation: Epa = -0.072pH + 0.58(R) 2 =0.9998). The slope of the calibration curve, -0.072 V, is close to the theoretical value of -0.059 V, indicating that the number of electrons transferred in this electrochemical reaction is equal to the number of protons. This proves that the oxidation reaction of doxorubicin hydrochloride on Pd-Au / MoS2 / GO / GCE is an isoelectronic and isoprotonal process. Example 7
[0038] The electrochemical sensor prepared in Example 3 was subjected to cyclic voltammetry studies in a PBS buffer solution containing 30 µM doxorubicin hydrochloride at pH 7.4 to explore the mechanism of doxorubicin hydrochloride detection by the constructed sensor. Scan rates were 40, 50, 60, 70, 80, 90, 100, 120, 140, 160, 180, 200, 250, 300, 350, and 400 mV / s. The results are as follows: Figure 6 As shown in Figure A, it can be observed that as the scan rate increases from 40 mV / s to 400 mV / s, the oxidation peak current of doxorubicin hydrochloride also gradually increases. The linear relationship between peak current and scan rate is shown in Figure A. Figure 6 B. The linear equation is: I pa =0.49υ + 21.27 (R) 2 =0.9981), which proves that the oxidation of doxorubicin hydrochloride on the Pd-Au / MoS2 / GO / GCE electrode is a surface adsorption controlled process. Example 8
[0039] The electrochemical sensor prepared in Example 3 was used to detect different concentrations of doxorubicin hydrochloride in PBS buffer solution at pH 7.4 using differential pulse cyclic voltammetry with Pd-Au / MoS2 / GN / GCE. The results are as follows: Figure 7As shown in Figure A, it can be observed from the figure that as the concentration of doxorubicin hydrochloride increases from 1.04 μmol / L to 54.5 μmol / L, the oxidation peak current of doxorubicin hydrochloride also gradually increases. Figure 7 B is the graph showing the relationship between peak current and the concentration of doxorubicin hydrochloride. The linear equation is: I(μA) = -0.043C(μmol / L) - 4.04(R) 2 =0.9990). The detection limit is 0.10 μmol / L.
[0040] The linear range of the detection was 1.04 μmol / L to 54.5 μmol / L.
[0041] like Figure 7 As shown in Figure -A, the peak current increases sequentially with the increase of doxorubicin hydrochloride concentration; like Figure 7 As shown in -B, the linear range of this sensor for the detection of doxorubicin hydrochloride is 1.04 μmol / L-54.5 μmol / L, and the detection limit is 0.10 μmol / L.
[0042] The sensor constructed using Example 3 was used to investigate the electrochemical response of doxorubicin hydrochloride on the Pd-Au / MoS2 / GO / GCE surface in the presence of other samples. Doxorubicin hydrochloride was detected in PBS buffer solution at pH 7.4 with concentrations of 40 μmol / L uric acid, 100 μmol / L glucose, 30 μmol / L dopamine, and 100 μmol / L ascorbic acid, respectively. The results showed that the oxidation peak current of doxorubicin hydrochloride was almost unaffected by the addition of different concentrations of interfering substances, and the ratio of its current response was close to 1. Therefore, it can be demonstrated that the Pd-Au / MoS2 / GN / GCE sensor has excellent selective response.
[0043] The response stability and reproducibility of the Pd-Au / MoS2 / GN / GCE electrode were also investigated. After modifying the Pd-Au / MoS2 / GN / GCE electrode, differential pulse voltammetry was used to detect doxorubicin hydrochloride every three days in PBS buffer solution at pH 7.4 over a two-week period. After a two-week interval, the oxidation peak current of doxorubicin hydrochloride decreased by only 1.57%. Furthermore, five independent Pd-Au / MoS2 / GO / GCE electrodes were prepared, and differential pulse voltammetry was used to determine doxorubicin hydrochloride in PBS buffer solution at pH 7.4. The results showed that the oxidation current response values of the five independent electrodes to doxorubicin hydrochloride were almost identical. These results demonstrate the good stability and reproducibility of the Pd-Au / MoS2 / GO / GCE electrode. Example 9
[0044] The Pd-Au / MoS2 / GN / GCE sensor constructed in Example 3 was used to detect doxorubicin hydrochloride in actual samples. A portion of urine was collected in a centrifuge tube, centrifuged, and the supernatant was added to 9 volumes of PBS buffer solution (pH=7.4). 9.2 mL, 9.0 mL, and 8.8 mL of the supernatant were added to an electrolytic cell cup to detect blank samples without doxorubicin hydrochloride. After detection, 0.8 mL, 1.0 mL, and 1.2 mL of 300 μmol / L doxorubicin hydrochloride were added to the blank samples to construct a three-electrode system for differential pulse voltammetry detection of doxorubicin hydrochloride in the solution.
[0045]
[0046] As shown in Table 3, the RSD of the proposed sensor for the detection of doxorubicin hydrochloride in urine is between 0.7% and 3.1%, indicating that the constructed Pd-Au / MoS2 / GN / GCE sensor can be used for the determination of actual samples.
[0047] Pd-Au / MoS2 / GN composite nanomaterials were successfully prepared using the method described in this invention. The prepared nanomaterials were characterized by SEM and XRD. The prepared Pd-Au / MoS2 / GN composite nanomaterials were used to construct an electrochemical sensor for the detection of doxorubicin hydrochloride. The results showed that the constructed Pd-Au / MoS2 / GN / GCE electrochemical sensor had high electrocatalytic activity for the detection of doxorubicin hydrochloride. The sensor showed good linearity for doxorubicin hydrochloride in the range of 1.04 μmol / L to 54.5 μmol / L, with a detection limit of 0.10 μmol / L. Furthermore, the constructed sensor exhibited good reproducibility, selectivity, and stability, and can be used for the detection of practical samples.
[0048] The above descriptions are merely some embodiments of the present invention. Those skilled in the art can make various modifications and improvements without departing from the inventive concept of the present invention, and these all fall within the scope of protection of the present invention.
Claims
1. A method for preparing Pd-Au / MoS2 / GO composite nanomaterials, characterized in that, Includes the following steps: S1. Disperse and mix a solution of GO, Na2MoO4 and CH4N2S in a certain mass ratio, heat it to a predetermined temperature and keep it at that temperature, then centrifuge and wash it to obtain MoS2 / GO composite nanomaterials. S2, The MoS2 / GO composite nanomaterials obtained in step S1 are combined with C6H5Na3O7 . 2H2O was mixed and dissolved in water and stirred at a certain temperature; HAuCl4·4H2O was added dropwise, and the mixture was kept warm and stirred for 20-40 min; K2PdCl6 and ascorbic acid were added dropwise, and the mixture was kept warm and stirred for 1.5 h-4 h; the mixture was washed and separated to obtain the Pd-Au / MoS2 / GO composite nanomaterial.
2. The method for preparing Pd-Au / MoS2 / GO composite nanomaterials according to claim 1, characterized in that, Step S1 includes the following steps: dissolving GO, Na2MoO4 and CH4N2S in water at a certain mass ratio, dispersing them evenly, then transferring the dispersion into a high-pressure reactor, heating it to a predetermined temperature, keeping it warm, separating and washing it to obtain MoS2 / GO composite nanomaterials.
3. The method for preparing Pd-Au / MoS2 / GO composite nanomaterials according to claim 2, characterized in that, In step S1, the mass ratios of GO, CH4N2S and Na2MoO4 are 1:7.96:6.38, 1:6.99:5.10, 1:5.97:4.80, and 1:5.00:3.
98.
4. The method for preparing Pd-Au / MoS2 / GO composite nanomaterials according to claim 2, characterized in that, In step S1, the GO, Na2MoO4 and CH4N2S solution is mixed and heated at 200°C for 24 hours.
5. The method for preparing Pd-Au / MoS2 / GO composite nanomaterials according to claim 1, characterized in that, In step S2, the mass ratio of MoS2 / GO, HAuCl4·4H2O and K2PdCl6 is 100:3.07:3.96, 100:4.42:5.78, or 100:17.79:23.
74.
6. The method for preparing Pd-Au / MoS2 / GO composite nanomaterials according to claim 1, characterized in that, In step S2, the insulation temperature is room temperature or 98°C.
7. The method for preparing Pd-Au / MoS2 / GO composite nanomaterials according to claim 1, characterized in that, In step S2, after adding the ascorbic acid reducing agent, the reaction time is 1.5h-4h.
8. A Pd-Au / MoS2 / GO composite nanomaterial prepared by the method according to any one of claims 1-7.
9. An electrochemical sensor, characterized in that, The electrochemical sensor is obtained by modifying a glassy carbon electrode with the Pd-Au / MoS2 / GO composite nanomaterial as described in claim 8.
10. The application of the electrochemical sensor according to claim 9 in the detection of doxorubicin hydrochloride.
Citation Information
Patent Citations
Molybdenum disulfide / graphene (MoS2 / rGo) lithium ion battery negative electrode material and preparation method of material
CN103904334A